ANALISIS LIKUIDITAS PADA KOPERASI SANGKIMA JAYA DI SANGATTA KABUPATEN KUTAI TIMUR TAHUN 2017 - Murfat Effendi, Hadi Mukhlison Mardiana (EKONOMIA, 2020)
ABSTRACT2018. Faculty of Economics, University August 17, 1945.Liquidity Ratio Analysis at Sangkima Jaya Cooperative in Sangatta Regency of East Kutai, under guidance. Mrs. Mardiana and Mr. Murfat Effendi.The formulation of the problem of whether liquidity in terms of current ratio, quick ratio, and cash ratio in the financial statements Sangkima Jaya Cooperative in Sangatta in 2017 higher than in 2016 This research was conducted at Sangkima Jaya Cooperative. Data sources include premier and secondary data. Data collection techniques use interviews to related parties and observationsThe basic theory used in this research is financial management. While the analytical tool using a balance sheet, SHU calculations, reports change balance. It also uses liquidity ratio consisting of current ratio, quick ratio, and cash ratio            From the calculation of liquidity in terms of current ratio in 2017 amounted to 195% increased 24% compared to the year 2016 of 171%. quick ratio in 2017 of 181.62% increased 22.62% compared to the year 2016 of 159%. cash ratio in 2017 amounted to 146% increased 23% compared to the year 2016 at 123%. This situation indicates that liquidity of cooperatives is increasingly liquid with an increase in the ability of short-term debt repayment. Thus, the hypothesis proposed that "Liquidity in terms of current ratio, quick ratio, and cash ratio in 2017 is higher than the year 2016 received.